POLÍTICAS PÚBLICAS DE ATIVIDADES FÍSICAS DE LAZER PARA PROMOÇÃO DA SAÚDE DISCENTE EM UNIVERSIDADES FEDERAIS NA REGIÃO CENTRO-OESTE, BRASIL - ALEX CAIÇARA DE ALBUQUERQUE (2025)
Entering higher education is marked by numerous changes in everyday life. Over the past two decades, the profile of students at federal universities has been characterized by individuals who balance both academic and work-related activities, which directly impacts their engagement in leisure-time physical activity. Such activities provide physical, psychological, social, emotional, and political benefits. However, participation in these experiences occurs unevenly, as multiple ecological factors act as barriers. In this context, the objective of the research was to analyze public policies on leisure-time physical activity aimed at students and their relationship with health promotion in federal universities located in the Midwest region of Brazil. Specifically, it sought to identify the existence of leisure-time physical activity programs directed toward student health promotion; to analyze the origins of the programs developed; and to examine the possibilities and limitations of these programs in contributing to health promotion. This is a qualitative study, with cross-sectional and longitudinal analyses, of an exploratory and documentary nature. The research examined the guidelines of the University Second Half Program (2009 to 2023), the National Student Assistance Policy, the Institutional Development Plan, and the User Service Charter, in addition to the regulations governing sports and leisure-time physical activity policies, within the time frame of 2020 to 2024, in federal universities in Brazil’s Midwest region. The University Second Half Program presents an innovative and relevant approach to leisure-time physical activity for students, with the potential to reduce the barrier of lack of time. However, the decline in the number of beneficiaries constitutes a significant limitation. The program maintains a focus on comprehensive development, incorporating objectives related to health promotion, the adoption of a physically active lifestyle, and the reduction of sedentary behavior as of 2020. Nevertheless, its reach is limited and selective, being present in only a few universities. Continuity is also restricted, as most institutions benefited from the program only once. Within the scope of the Student Assistance Policy, sports are included in the regulations of UFGD, UFCat, UFJ, and UFG, but absent in the others. Among the areas contemplated, only student housing and food services were present in all institutions analyzed. A total of 24 initiatives were identified, with a predominance of leisure-time physical activity actions registered in the Institutional Development Plan, the User Service Charter, and internal regulations. The main type of support identified was service provision, with a predominance of sporadic activities. It is concluded that, although there are initiatives aimed at leisure-time physical activity, their occurrence remains heterogeneous. While some institutions present high levels of activity, others develop few or none. Even with mechanisms such as the University Second Half Program and the National Student Assistance Policy, initiatives remain limited, highlighting the absence of a specific funding source and a structured policy for consolidation. In most cases, such actions are punctual and short-lived, which undermines their continuous development and directly impacts the promotion of student health through leisure-time physical activity.